Counter-governance and ‘post-event prevent’: Regulating rumours, fake news and conspiracy theories in the aftermath of terror - Innes, Martin (International journal of law, crime and justice, 2023)
Framed by ongoing debates about both the legitimacy and efficacy of the UK government's Prevent counter-terrorism strategy, this article examines how and why it is resisted and contested in both overt and more nuanced ways. The analysis focuses specifically upon how such contests are manifested in the aftermath of terror events illuminated by two distinct data sources. These are empirical data collected from interviews with policy developers and deliverers, together with material derived from systematic monitoring and assessment of social media following four terror attacks in the UK in 2017. It is suggested that such incidents are singularly important moments because they simultaneously evidence the need for Prevent-type interventions, but also such interventions' apparent failures to stop such violence. A key theme for the article concerns how, situated in the contemporary information environment, a key strand of Prevent work conducted in the wake of terrorist violence involves managing the potential impacts of rumours, conspiracy theories and other disinformation. The management of public perceptions and reputation thus emerge as vital undertakings. Insights from the data are used to develop a more conceptually oriented argument concerning the logics and rationalities of ‘counter-governance’, positioning it in a wider literature on de-centred governance and regulation.